Estimating occupational mobility with covariates - Jørgen Modalsli (Statistics Norway, Research Department, 2015)
The Altham statistic is often used to calculate intergenerational associations in occupations in studies of historical social mobility. This paper presents a method to incorporate individual covariates into such estimates of social mobility, and to construct corresponding confidence intervals. The method is applied to an intergenerational sample of Norwegian data, showing that estimates of intergenerational mobility are robust to the inclusion of controls for father's and son's age.
Keywords: J62; N34; C46; 330; Intergenerational occupational mobility; Altham statistic